Estimating the correlates of female labour force participation in Bangladesh: 2005 to 2010 - Alam, Afroza (My University, 2018)
The government of Bangladesh has targeted 8 percent gross domestic product (GDP) growth by 2020. To attain this, increasing labour force participation is particularly important as the country has a very large population. Male participation is already high, thus the focus needs to be on increasing female labour force participation, highlighting the importance of studying the factors associated with rising female labour force participation in Bangladesh. In this research report, I investigate both the demand- and supply-side correlates of female labour force participation through descriptive and econometric analysis of Bangladesh labour force survey data. Demandside analysis found that the economy has increased its capacity to absorb female labour as the economic structure has shifted from agriculture to the manufacturing and service sectors. Supplyside analysis found that individual and household characteristics are both important sets of factors explaining female labour force participation. Individual characteristics that are correlated with female labour supply include education, marital status, training, age, and religion, while household characteristics include the number of children, household income, and household size. Econometrics analysis shows that these variables have a significant relationship with female labour force participation. Non-linear decomposition techniques (Gomulka and Stern, 1990) identified some of the charactertistics of women that have been changed over the years (including the share of women with prior training and the share in middle income households), helping to explain the increase in their labour force participaton. However, changes in women’s labour force participation are primarily explained by changes in the relationship between characteristics and labour supply (i.e. changes in the coefficients). For example, women from lower income households, and households with fewer children were significantly more likely to participate in the labour force in 2010 than they had been in 2005.
A research report submitted in partial fulfilment of the requirement for the degree of Masters in Development Theory and Policy to the Faculty of Commerce, Law and Management School of Economic and Business Sciences, University of the Witwatersrand, Johannesburg, 2010
Keywords: Labor supply--Developing countries; Women--Employment--Developing countries